(untitled) (Research, Society and Development, 2021)
This study proposes, as the main objective, to produce a professional qualification course that allows the educators to comprehend how to apply and develop active-teaching methodologies that enable meaningful learning through the Design Thinking. For this, an exploratory and descriptive research within an qualitative approach was carried out in a public basic education institution, located in the southern region of Minas Gerais. It was used as a data collection method, the semi-structured interview and, for the data analysis the codification method. At the end, it was possible to develop a qualification course that aimed to favor the understanding about the importance of applying active methodologies that allow meaningful learning, as well as, the understanding regarding the use of Design Thinking for the development of such methodologies.